Forage legume productivity in a medium altitude acid soil area of Ethiopia - Lazier, John R. (French Grassland Society, 1989)
A study conducted to determine the productivity of promising forage legumes in mixture with a commercial cultivation of a grass dominant pasture in Soddo area (Ethiopia)